2012
DOI: 10.1021/cs300472p
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Co–B Amorphous Alloy in Uniform Spherical Nanoparticles with Enhanced Catalytic Properties

Abstract: Control of the size and morphology of metallic nanomaterials enables mastery of their properties to enhance their catalytic performances. In this work, uniform Co−B amorphous alloy nanoparticles were synthesized by a simple chemical reduction of [CoX 4 ] − with BH 4 − in the presence of Bu 4 P + . With the characterization of X-ray diffraction, selective area electronic diffraction, X-ray photoelectron spectroscopy, differential scanning calorimetry, and transmission electron microscopy, the resulting Co−B sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 2 more Smart Citations
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
“…Apart from the common amorphous nanospheres composed of CaCO 3 and Si, and amorphous nanospheres of some other compounds, such as Se [53], TiO 2 [54][55][56][57], Co-B alloy [58], FePO 4 [60] and zinc citrate [61], have also been prepared, generally by facile solution routes. Recently, Kuai et al [59] reported an interesting aerosol-spray-as- …”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the weaker coordination of halide ligands to metallic ions than that between NH 3 and metallic ions, 103 [CoX 4 ] 2À ions formed in the presence of KCl and Bu 4 PBr was used as cobalt sources for the preparation of Co-B amorphous alloy. 48 The simple reduction of [CoX 4 ] 2À ions with borohydride resulted in monodispersed and uniformly spherical NPs with an average particle size about 55 nm (Fig. 23).…”
Section: Amorphous Alloy Npsmentioning
confidence: 99%
“…Nanocomposites differ from the conventional composites due to the particularly high surface-to-volume ratio of ceramic reinforcement [3][4][5][6]. Amorphous materials have also attracted an increasing amount of attention due to their unique physical, mechanical and chemical properties [7][8][9][10]. LMD is a promising approach to producing the amorphous--nanocrystalline composites on metals.…”
Section: Introductionmentioning
confidence: 99%